2007
DOI: 10.1080/03014460701251112
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead level and physical fitness of schoolchildren in the copper basin of south-western Poland: Indirect effects through growth stunting

Abstract: Direct effects of blood lead level on indicators of physical fitness in school age youth are not evident. Blood lead level adversely affects physical fitness indirectly through growth stunting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…In comparing our SMBA results with literature data (Ahnert, 2005;Beck et al, 1995;Bös et al, 2009;Ignasiak et al, 2007;Monyeki et al, 2005;Olds et al, 2006;Roth et al, 2010;Schmid et al, 2007;Vandorpe et al, 2011), we observed that sixyear-old first graders performed better than the reference data, and eight-year-old first graders performed equally or worse. These findings underpin the fact that the criterion values we used should be considered arbitrary in the context of school-based assessments.…”
Section: Discussionsupporting
confidence: 72%
“…In comparing our SMBA results with literature data (Ahnert, 2005;Beck et al, 1995;Bös et al, 2009;Ignasiak et al, 2007;Monyeki et al, 2005;Olds et al, 2006;Roth et al, 2010;Schmid et al, 2007;Vandorpe et al, 2011), we observed that sixyear-old first graders performed better than the reference data, and eight-year-old first graders performed equally or worse. These findings underpin the fact that the criterion values we used should be considered arbitrary in the context of school-based assessments.…”
Section: Discussionsupporting
confidence: 72%
“…One of these described mercury exposure from gold mining in Indonesia [95], and one described blood lead levels in teenagers employed in an auto repair business in Turkey [102]. Two studies described occupational take-home exposures of lead in children living with parents who were employed in mining and smelting industries [64, 89]. Worker education and improved industrial hygiene practices are well-known interventions that could be implemented and have been effective in reducing occupational take-home exposures in developed countries.…”
Section: Resultsmentioning
confidence: 99%
“…In a Polish study of low-level prenatal lead exposure (median cord blood lead level = 1.23  μ g/dL), a significant deficit in Mental Development Index scores persisted at 1, 2, and 3 years of age [86]. Other health effects associated with lead exposure in these studies were low birth weight, aplastic anemia, and stunted growth [68, 71, 89]. …”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown an association between increase in BLL and decrease in stature. For each 10μg/dL increase in BLL, a reduction in height of about 1–3 cm has been seen [ 22 , 26 , 27 , 47 – 50 ]. A study in Poland proposed a biological basis for the relationship between BLL and height, suggesting that lead in the blood could interrupt matrix calcification, resulting in stunted long bone growth [ 51 ].…”
Section: Discussionmentioning
confidence: 99%